Photothermally Controlled Methotrexate Release System Using β-Cyclodextrin and Gold Nanoparticles - Nataly Silva; Ana Riveros; Nicolás Yutronic; Erika Lang; Boris Chornik; Simón Guerrero; Josep Samitier; Paul Jara; Marcelo J. Kogan (Nanomaterials, 2018)
The inclusion compound (IC) of cyclodextrin (CD) containing the antitumor drug Methotrexate (MTX) as a guest molecule was obtained to increase the solubility of MTX and decrease its inherent toxic effects in nonspecific cells. The IC was conjugated with gold nanoparticles (AuNPs), obtained by a chemical method, creating a ternary intelligent delivery system for MTX molecules, based on the plasmonic properties of the AuNPs. Irradiation of the ternary system, with a laser wavelength tunable with the corresponding surface plasmon of AuNPs, causes local energy dissipation, producing the controlled release of the guest from CD cavities. Finally, cell viability was evaluated using MTS assays for β-CD/MTX and AuNPs + β-CD/MTX samples, with and without irradiation, against HeLa tumor cells. The irradiated sample of the ternary system AuNPs + β-CD/MTX produced a diminution in cell viability attributed to the photothermal release of MTX.